Evaluate the integral:
You can use u {\displaystyle u} -substitution.
Thus,
Solution:
∫ tan 4 ( x ) d x = ∫ tan 2 ( x ) ( sec 2 ( x ) − 1 ) d x = ∫ tan 2 ( x ) sec 2 ( x ) d x − ∫ tan 2 ( x ) d x = ∫ tan 2 ( x ) sec 2 ( x ) d x − ∫ ( sec 2 x − 1 ) d x {\displaystyle {\begin{array}{rcl}\displaystyle {\int \tan ^{4}(x)~dx}&=&\displaystyle {\int \tan ^{2}(x)(\sec ^{2}(x)-1)~dx}\\&&\\&=&\displaystyle {\int \tan ^{2}(x)\sec ^{2}(x)~dx-\int \tan ^{2}(x)~dx}\\&&\\&=&\displaystyle {\int \tan ^{2}(x)\sec ^{2}(x)~dx-\int (\sec ^{2}x-1)~dx}\end{array}}}
∫ tan 4 ( x ) d x = u 3 3 − ( tan ( x ) − x ) + C = tan 3 ( x ) 3 − tan ( x ) + x + C . {\displaystyle {\begin{array}{rcl}\displaystyle {\int \tan ^{4}(x)~dx}&=&\displaystyle {{\frac {u^{3}}{3}}-(\tan(x)-x)+C}\\&&\\&=&\displaystyle {{\frac {\tan ^{3}(x)}{3}}-\tan(x)+x+C.}\end{array}}}
Return to Sample Exam